THE CONCEPT OF THE FOOD REGIME AND TRENDS IN THE DEVELOPMENT OF THE FOOD SITUATION IN THE MODERN WORLD. Концепция Продовольственного Режима И Тенденции Развития Продовольственной Ситуации В Современном Мире - Malov, Alexander Vadimovich (2018)
This article is devoted to the study of the food regime, a concept little known in Russian academic literature. The author identifies the "theoretical and methodological platform" of the concept using a comparative approach and retrospective analysis. The ensemble of a comparative-historical approach, a method of analyzing secondary data and a forecasting method contributed to the consolidation of the concept of the food regime as a tool capable of streamlining the global stages of production, consumption and distribution of food in historical retrospect as well as in the foreseeable future. The author demonstrates that the consistent transformation of food regimes comes about due to the conflict between two principles, "protectionism" and "free trade," which are effectively adapted to different political and economic realities. The identified "sequence" is consistent with the general position of the theory of Karl Polanyi (the Double Movement) and allows us to assert that the foundation of the Fourth Food Regime will be based on a modified version of protectionism. This is confirmed by the growing popularity of the transnational movement La Via Campesina and the growing demand for its revolutionary strategy of Food Sovereignty. (English)
Political Science
Keywords: double movement; food regime; food security; food sovereignty; globalization; глобализация; двойное движение; продовольственная безо-пасность; продовольственный режим; продовольственный суверенитет